The words of Jesus in the Gospel of Thomas: the genesis of a wisdom tradition - Kim, David W. (Gnostica, 2021)
The transmission of a Thomas tradition -- The Thomasine community -- Hermeneutical debates over mystical Logia : sapiential versus gnostic -- The parables and kingdom language in Thomas -- The female disciples in Thomas.